2023
DOI: 10.1002/anie.202308775
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Metal‐Nitrogen Coupling in Anti‐Perovskite Nitride via Cation Doping for Efficient Reduction of Nitrate to Ammonia

Abstract: The complexes of metal center and nitrogen ligands are the most representative systems for catalyzing hydrogenation reactions in small molecule conversion. Developing heterogeneous catalysts with similar active metal‐nitrogen functional centers, nevertheless, still remains challenging. In this work, we demonstrate that the metal‐nitrogen coupling in anti‐perovskite Co4N can be effective modulated by Cu doping to form Co3CuN, leading to strongly promoted hydrogenation process during electrochemical reduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Therefore, an appropriate intensity of the HER can avoid a strong HER and retain sufficient H ads , which is another critical consideration for the hydrogenation reaction of nitrogen intermediates. According to adsorption configurations of different catalysts (Figure S5), Figure f shows the Gibbs free energy of −2.4209, 1.3751, and −0.1374 eV for Cu 2– x S/MoS 2 , Cu 2– x S, and MoS 2 during the HER process, respectively, which demonstrates that MoS 2 is mainly used for activation of water to generate active hydrogen with near-zero free energy and the Cu 2– x S/MoS 2 interface has the strongest H* retention and adsorption ability . The change in the Gibbs free energy is shown in Table S4.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, an appropriate intensity of the HER can avoid a strong HER and retain sufficient H ads , which is another critical consideration for the hydrogenation reaction of nitrogen intermediates. According to adsorption configurations of different catalysts (Figure S5), Figure f shows the Gibbs free energy of −2.4209, 1.3751, and −0.1374 eV for Cu 2– x S/MoS 2 , Cu 2– x S, and MoS 2 during the HER process, respectively, which demonstrates that MoS 2 is mainly used for activation of water to generate active hydrogen with near-zero free energy and the Cu 2– x S/MoS 2 interface has the strongest H* retention and adsorption ability . The change in the Gibbs free energy is shown in Table S4.…”
Section: Resultsmentioning
confidence: 97%
“…This result is also confirmed by XPS where the binding energy of Co 0 peak in CoP@Co is 777.82 eV, lower than that of Co (777.94 eV) (Figure b) . According to density functional theory (DFT) calculations, CoP@Co forms *H more easily and the as-generated *H is more difficult to form H 2 than Co, suggesting that the surface of CoP@Co is more prone to *H accumulation (Figure c). , To verify the existence of *H, the electrochemical quasi in situ electron paramagnetic resonance (EPR) is studied . The EPR spectra of CoP@Co and Co (in 1.0 M KOH solution at −0.2 V vs RHE) are recorded using 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) as the H-radical trapping reagent (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…With the introduction of CoP, the energy barrier in the rate-limiting step (Co: *N to *NH, 3.02 eV; CoP@Co: *NO to *NOH, 0.45 eV) changes, which is consistent with the ultralow overpotential of CoP@Co for NRA. To be specific, a more negative value of projected crystal orbital hamilton population (−pCOHP) indicates that the intermediate *N is in a more stable state on CoP@Co, which is favorable for the subsequent hydrogenation to NH 3 …”
Section: Resultsmentioning
confidence: 99%
“…Electroreduction of NO 3 − to ammonia (NRA) represents a prospective route for both high‐value‐added NH 3 synthesis and wastewater treatment, where the design of high‐efficiency electrocatalysts to drive the complex electron–proton‐coupled process is crucial. [ 99,100 ] Very recently, two kinds of nc ‐MOFs, Ni‐HHTP (denoted as Ni‐O 4 ‐CCP) and Ni‐HITP (Ni‐N 4 ‐CCP) were applied as electrocatalysts to investigate the impact of coordination environment on NRA performance. [ 101 ] The electrochemical results showed that Ni‐O 4 ‐CCP exhibited a higher NH 3 yield rate of 1.83 mmol h −1 mg −1 ( Figure a) and Faraday efficiency of 94.7% (Figure 18b).…”
Section: Applicationsmentioning
confidence: 99%